Abundance and Length-Weight Relationship of Fishes from Sungai Sepang Besar, Selangor - A Ya, N; R Singh, H (International Journal of Engineering and Technology, 2019)
This study was conducted to determine the abundance and the length-weight relationship of fishes of Sungai Sepang Besar (SSB), Selangor. A total of 832 individuals from 32 families comprising 50 species were collected from April 2014 to February 2015 by utilizing gill nets of various mesh size (1.25, 2.25, 2.50, 2.75, 3 and 4.5 inch) and long lines. The family Toxotidae was most abundant with a total of 474 individuals sampled comprising 2 species namely, Toxotes jaculatrix (n=288) and Toxotes chatareus (n=186). The Shannon-Weiner Index (2.37) and the Pielou Evennes (0.21) was low but the Margalefâ€™s richness (7.29) was relatively high. Arius sagor, Photopectoralis bindus, Toxotes jaculatrix, Thryssa dussumieri, and Stolephorus indicus demonstrated positive allometric growth (b>3) while Plotosus lineatus and Toxotes chatareus showed negative allometric growth (b<3). Understanding abundance and the length-weight relationship of fish is important not only for species conservation and management, but also their habitat use.Â Â Â